Managing chronic pain in adults with haemophilia: current status and call to action. (2nd October 2014) - Humphries, T. J.; Kessler, C. M.
Summary Haemophilic arthroses are associated with acute pain during bleeding episodes and with chronic pain caused by arthritic complications of repeated bleeding into joints. Unlike other conditions (e.g. osteoarthritis, rheumatoid arthritis, sickle cell disease), there are limited data on pain management in haemophilia. Management of arthritic individuals and those with sickle cell disease relies heavily on administration of acetaminophen, non‐steroidal anti‐inflammatory drugs (NSAIDs) and opioid analgesics. In haemophilia, acetaminophen often has limited efficacy at therapeutic doses, offering a narrow dosing range in those with liver disease due to chronic hepatitis C. NSAIDs can effectively manage pain in patients with haemophilia, but these agents are potentially associated with a significant risk of precipitating or exacerbating bleeding complications in an already coagulopathic population. Opioids have proven effective in osteoarthritis and sickle cell disease, but outcomes data in those with haemophilia are virtually non‐existent. Patients with haemophilia are at least as vulnerable as other chronic pain populations to opioid‐related adverse events and to developing abusive behaviours and addiction. Despite pain management strategies for patients with haemophilia being far from optimal, the predominant precept of haemophilia management still applies. As such, it is critically important to aggressively reverse or prevent acute symptomatic bleeding in a timely and effective manner to at least minimize pain and progressive joint damage. This review should serve as a call to action to prioritize pain management in haemophilia care and spur interest in the development, improvement and standardization of tools to assess and manage acute and chronic pain in haemophilia.